Significance of MRI Guided Focused Ultrasound Thalamotomy for Parkinson’s Disease: A Review - Pooja, N.A.; Pahuja, S.K.; Veer, K. (Current Medical Imaging, 2021)
Background: Magnetic-Resonance guided Focused Ultrasound (FUS) thalamotomy is a new and less invasive surgical technique for treating Parkinson’s disease (PD). During therapy, the required part of the cerebral (as STN, Internal Globus Pallidus, and Ventral Intermediate Nucleus) is ablated with less possibility of infection and brain hemorrhage as it normally happens in invasive procedures. Introduction: New advancement in the technique enables it for transcranial transportation of US. Nowadays, US coupling with MRI confirms the accurate energy transferring and monitoring. So, MRI guided FUS lesioning is discovered for various psychiatric and brain disorders. Methods: A technical overview of non-invasive MRI-FUS thalamotomy to treat various tremors is described here. Research, review articles, and book chapters are extracted from online resources using related search strings from the year 1994-2020. Results: MRgFUS is concluded a non-invasive, satisfactory, and safe technique to reduce the tremor. Conlusion: MRgFUS is comparatively a new method that is being explored as a non-invasive cerebral ablation to solve the problems of movement disorder.
Keywords: magnetic resonance imaging